Learners’ perception of OUM video lectures - P. Rajesh Kumar; Woo Tai Kwan; Nazrai Ahmad Zabidi; Evy Sofia Ariffin (2019)
Leveraging on information and communication technology (ICT) has enabled education providers to come up with creative ways of engaging with learners. As a result, learners are constantly being exposed to new ways of learning and collaborating with their peers. Also, accessibility to affordable smart devices with fast connections has only intensified the integration of technology into the education sphere. Open University Malaysia (OUM) has long recognised this trend and has been actively developing various tools to deliver its learning materials through the online model. One such tool is its online video lectures. This paper describes an exploratory study of OUM learners’ perception of video lectures for certain courses in their studies. The study is based on a survey questionnaire to determine learners’ expectations and preferences for the video lectures used in OUM and also on what other additional features, if any, should be included. The motivation of this research is to help the institution make an informed decision on the future development of video lectures based on the feedback of learners so that they are aligned with the expectations of OUM learners. (Abstract by authors)